Band Alignment at Heteroepitaxial Perovskite Oxide Interfaces. Experiments, Methods, and Perspectives. Issue 11 (10th May 2017) - Giampietri, Alessio; Drera, Giovanni; Sangaletti, Luigi
Abstract : Recent advances in the growth of epitaxial oxide thin films have fostered a steady increase of research on perovskite oxide heterojunctions, which are now produced with unprecedented quality. Applications of these ultra‐thin interfaces in the field of electronics, photon harvesting, photovoltaics and photocatalysis strongly rely on the capability to master band gap engineering at the nanoscale. In this report the band gap alignment at all‐oxide perovskite interfaces is reviewed, with focus on oxide perovskite layers grown on SrTiO3, as these systems can display a two dimensional electron gas at the interface, disclosing possible applications in the next‐generation nanoelectronic devices. Papers reporting an experimental determination of band diagram are considered. The most reliable methods to experimentally track the band alignment at the interface are presented, based on photoelectron spectroscopy analysis of core level or valence band structures, including recent resonant photoemission spectroscopy studies. Experimental data from several conducting and insulating SrTiO3 ‐based heterostructures are presented and results are discussed through comparison with theoretical predictions. It is shown that electron spectroscopies are a powerful tool to investigate band alignment and to address band engineering issues, filling the gap between theoretical predictions and a relatively limited experimental dataset. Abstract : The band gap alignment at all‐oxide perovskite interfaces is reviewed, with focus on layers grown on SrTiO3 . These heterojunctions are currently produced with unprecedented quality and future applications will rely on the capability to master band gap engineering at the nanoscale. It is shown that electron spectroscopies are a powerful tool to address band engineering issues, bridging the gap between theoretical predictions and experimental results.